Frontispiece: Electronic Oxide–Metal Strong Interaction (EOMSI). Issue 60 (29th October 2020) - Qian, Kun; Duan, Huimei; Li, Yangyang; Huang, Weixin
Abstract : The effect of oxide–metal interactions on the structures and catalytic performances of oxide adlayers supported on metal substrates can be described by using the concept of strong oxide–metal interaction of oxide/metal inverse catalysts. The applicability of this concept is demonstrated by using CeO x adlayers supported on Ag nanocrystals. Read more in the Concept by W. Huang et al. on page 13538 ff.